2016
DOI: 10.1016/j.ypmed.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The role of neighborhood characteristics and the built environment in understanding racial/ethnic disparities in childhood obesity

Abstract: Background Childhood obesity prevalence remains high and racial/ethnic disparities may be widening. Studies have examined the role of health behavioral differences. Less is known regarding neighborhood and built environment mediators of disparities. The objective of this study is to examine the extent to which racial/ethnic disparities in elevated child body mass index (BMI) are explained by neighborhood socioeconomic status (SES) and built environment. Methods We collected and analyzed race/ethnicity, BMI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…28,29 A study from Massachusetts showed a much stronger reduction in the association with childhood obesity when adjusting for socioeconomic status compared with adjusting for the built environment characteristics. 30 While income plays a role in the development of obesity, our data suggest that community resources may not be the primary driver. The assessment in the NSCH queries presence and not quality of resources, and notably, the perception of a safe, supportive neighborhood across income strata varied two-fold.…”
Section: Discussionmentioning
confidence: 70%
“…28,29 A study from Massachusetts showed a much stronger reduction in the association with childhood obesity when adjusting for socioeconomic status compared with adjusting for the built environment characteristics. 30 While income plays a role in the development of obesity, our data suggest that community resources may not be the primary driver. The assessment in the NSCH queries presence and not quality of resources, and notably, the perception of a safe, supportive neighborhood across income strata varied two-fold.…”
Section: Discussionmentioning
confidence: 70%
“…Many childhood obesity prevention interventions are implemented in communities across the United States, yet disparities in dietary intake and obesity rates by region, ethnic group and income level persist . Better understanding of whether interventions are having the intended effects, particularly on the most vulnerable populations, is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Empirically, neighborhood environments have been linked to a wide range of child health outcomes including body mass index (BMI) (Chen & Paterson, 2006), overweight and obesity (Alvarado, 2016; Borrell, Graham, & Joseph, 2016; Sharifi et al, 2016), asthma and (McGrath, Matthews, & Brady, 2006) and blood pressure. (T.…”
Section: Empirical Reviewmentioning
confidence: 99%